Complete chloroplast genome of Chilean needle grass, Nassella neesiana (Poaceae: Stipeae) - Aisuo Wang; Hanwen Wu; David Gopurenko (Mitochondrial DNA. Part B. Resources, 2017)
Nassella neesiana (Chilean needle grass) is a serious weed in Australia, and has been included in the list of Weeds of National Significance (WoNS). We present here, the complete chloroplast sequence of N. neesiana reconstructed from Illumina whole genome sequencing. The complete chloroplast sequence is 137,700 bp in size, and has similar gene content and structure as other published chloroplast genomes of Stipeae. The N. neesiana chloroplast genome is deposited at GenBank under accession number MF480752.